2020
DOI: 10.3390/molecules25204685
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial and Antioxidant Activities of Lactobacillus coryniformis BCH-4 Bioactive Compounds and Determination of their Bioprotective Effects on Nutritional Components of Maize (Zea mays L.)

Abstract: Lactic acid bacteria (LAB) can synthesize antimicrobial compounds (AMCs) with nutritional and bioprotective properties in crops and food products. In the current study, AMCs of Lactobacillus coryniformis BCH-4 were evaluated to control fungal spoilage in maize grains. On maize grains treated with 75%–100% (v/v) concentrated AMCs, no fungal growth was observed even after 72 h of Aspergillus flavus inoculation. Proximate analysis of treatments A1 (raw grains), A2 (A. flavus inoculated grains) and A3 (A. flavus +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Despite this, the present study first time described the significant improvement of antifungal potential in CFS treated T3 maize grains by improving its functional antioxidant contents. This finding was supported by our previous study [ 31 ] that the CFS of Loig . coryniformis BCH-4 had potent antioxidant potential by observing its DPPH scavenging activity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Despite this, the present study first time described the significant improvement of antifungal potential in CFS treated T3 maize grains by improving its functional antioxidant contents. This finding was supported by our previous study [ 31 ] that the CFS of Loig . coryniformis BCH-4 had potent antioxidant potential by observing its DPPH scavenging activity.…”
Section: Discussionsupporting
confidence: 89%
“…Agar well diffusion assay was performed for determining the antifungal potential of Loig . coryniformis BCH-4 CFS [ 31 ]. For this purpose, the A .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, antimicrobial compounds produced by Lactobacillus coryniformis BCH-4 have been shown to inhibit the growth of Aspergillus flavus, a cause of fungal spoilage, in maize grains. In addition, 2-oxopropanoic acid, 2-hydroxypropane-1,2,3-tricarboxylic acid, 2-hydroxybutanedioic acid, 2-hydroxypropanoic acid, propanedioic acid, and butanedioic acid have been identified as bioactive compounds among the antimicrobial compounds isolated from L. coryniformis [31]. It has been reported that bacteriocin produced by L. paracasei WX322 severely affected Pectobacterium carotovorum, a soft rot pathogen in vegetables [32].…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma asperellum [14], Pseudomonas sp. [15], and many acid lactic bacteria (LAB) like Lactobacillus plantarum [16,17], Lactobacillus coryniformis [18], or Leuconostoc mesenteroides [4].…”
Section: Introductionmentioning
confidence: 99%